The Effect of PjBL-Based Electronic LKPD Integrated with STEM on Reaction Rate Material on Problem-Solving Ability and Self-Efficacy of Students - Halimatuzzahra*, Halimatuzzahra; Louise, Isana Supiah Yosephine; Kamari, Azlan bin (Universitas Syiah Kuala, 2025)
Problem-solving skills can be influenced by the independent curriculum currently used in Indonesia. Merdeka curriculum gives schools the freedom to design learning programs that align with student needs and local conditions. This quantitative research aims to analyze the effect of using electronic student worksheet (LKPD) based on STEM-integrated project based learning (PjBL) on the problem-solving ability (PSA) and self-efficacy of students simultaneously or individually. This research is a quasi-experimental research with a posttest-only control group design. The trial was conducted at SMAN 13 Banjarmasin consisting of one experimental class and one control class selected using a random sampling technique of the class. Data on the PSA and self-efficacy of students obtained from experimental and control classes were analyzed using the Manova test. The results of this study indicate the influence of PSA and student self-efficacy simultaneously and respectively. The effective contribution to PSA and self-efficacy of students simultaneously is 0.419 in the very large category. In addition, the effective contribution to students' PSA is 0.225, and to students' self-efficacy is 0.379, both of which fall into the very large category.